Topical Aloe Vera (Aloe barbadensis Miller) Extract Does Not Accelerate the Oral Wound Healing in Rats. (16th April 2015) - Coelho, Fernanda Hack; Salvadori, Gabriela; Rados, Pantelis Varvaki; Magnusson, Alessandra; Danilevicz, Chris Krebs; Meurer, Luise; Martins, Manoela Domingues
<x xml:space="preserve">Abstract</x> The effect of topical application of Aloe Vera (Aloe barbadensis Miller) extract was assessed on the healing of rat oral wounds in an in vivo model using 72 male Wistar rats divided into three groups (n = 24): control, placebo and Aloe Vera (0.5% extract hydroalcoholic). Traumatic ulcers were caused in the dorsum of the tongue using a 3‐mm punch tool. The Aloe Vera and placebo group received two daily applications. The animals were sacrificed after 1, 5, 10 and 14 days. Clinical analysis (ulcer area and percentage of repair) and histopathological analysis (degree of re‐epithelialization and inflammation) were performed. The comparison of the differences between scores based on group and experimental period, both in quantitative and semi‐quantitative analyses, was performed using the Kruskal–Wallis test. The significance level was 5%. On day 1, all groups showed predominantly acute inflammatory infiltrate. On day 5, there was partial epithelialization and chronic inflammatory infiltrate. On the days 10 and 14 total repair of ulcers was observed. There was no significant difference between groups in the repair of mouth ulcers. It is concluded that treatment using Aloe Vera as an herbal formulation did not accelerate oral wound healing in rats. Copyright © 2015 John Wiley & Sons, Ltd.